Importancia del órgano de solución de diferencias en la OMC en los mercados internacionales - Macías Muentes, Tatiana Stefanía (2017)
The purpose of this paper is to determine the importance of the WTO Dispute Settlement Body in the negotiations on international market access. The area under investigation is the functioning of the WTO, especially how it resolves the differences between countries, especially taking into account the cost-benefit analysis that is incurred. The research is carried out through the revision of primary and secondary sources with a qualitative and comparative approach as well as an analytical and descriptive perspective. The result obtained after studying two cases specifically in Ecuador, shows us how the organism provides good opportunities for commercial development worldwide with resource savings. It is recommended that countries raise awareness and allow these agencies to advise them when making decisions and resolve conflicts in search of a more efficient and effective trade.